Hypnobreastfeeding Meningkatkan Pengeluaran Asi Pada Ibu Nifas - Gaparini, Alifiani; Astutik, Linda Puji; Meyasa, Lola (Jurnal Kebidanan Malakbi, 2024)
Hypnobreastfeeding, a relaxation technique that incorporates positive affirmations, has emerged as a promising strategy for enhancing milk production in postpartum women. By inducing a state of deep relaxation and focusing the mind on positive thoughts, hypnobreastfeeding can stimulate the release of prolactin and oxytocin, hormones crucial for milk synthesis and letdown. This study aimed to investigate the impact of hypnobreastfeeding on breastfeeding expenditure in postpartum women at UPTD Pahandut Health Center. A pre-experimental design with a one-group pretest-posttest approach was used. This design involved measuring participants' outcomes before and after the intervention, allowing for an assessment of any changes that occurred. The total sample size consisted of 36 individuals. The results of the study demonstrated a significant increase in milk production among the participants (p-value = 0.000). This suggests that hypnobreastfeeding can be an effective tool for augmenting milk supply, particularly for women facing challenges in breastfeeding. Hypnobreastfeeding offers a promising approach for increasing milk production in postpartum women. The findings of this study suggest that it can be a valuable tool for supporting breastfeeding and promoting the health and well-being of both mother and infant.